Enset landrace diversity in major enset growing regions of Southern Ethiopia - Blomme, Guy; Kearsley, Elizabeth; Buta, Sisay; Chala, Alemayehu; Kebede, Ruhama; Addis, Temesgen; Yemataw, Zerihun (African Crop Science Society, 2023)
Enset [Ensete ventricosum (Welw.) Cheesman] is an important food security crop of the Southern Ethiopian highlands. The cultivation of enset is characterised by a wide variety of landraces, suitable to varying agro-ecological conditions and with multiple uses by households. The objective of this paper is to present enset landrace diversity, characteristics and uses in Ethiopia. The study was done through interviews with 375 households covering 20 communities (kebeles) and eight ethnic groups, along an altitudinal range of 1,500 to 3,000 masl across the main enset-producing belt in Southern Ethiopia. A total of 296 locally named enset landraces were recorded. Landrace presence was mostly constrained at the kebele and zone levels, with limited overlap in landrace names across these boundaries. Moderate to high enset landrace diversity was observed on farms across the entire study region. Cultivating a variety of landraces not only allowed for diversified uses, but increases the likelihood of retained yield and food security under variable environmental circumstances. Farmer experience and indigenous knowledge allow for the selection of specific landraces suited to prevalent agro-ecological conditions. We identified a perception bias in the attribution of landrace agro-ecological characteristics, with farmer insight often dependent on the environmental conditions that the local community was exposed to. We underscore the importance of research-based characterisation of enset landraces, to ensure optimal cultivation of this food security crop in changing climatic conditions.